Dynamic reorganization of photosynthetic supercomplexes during environmental acclimation of photosynthesis - Minagawa, Jun (Frontiers in Plant Science, 2013)
Plants and algae have acquired the ability to acclimate to ever-changing environments in order to survive. During photosynthesis, light energy is converted by several membrane protein supercomplexes into electrochemical energy, which is eventually used to assimilate CO2. The efficiency of photosynthesis is modulated by many environmental factors such as quality and quantity of light, temperature, drought, and CO2 concentration, among others. Accumulating evidence indicates that photosynthetic supercomplexes undergo supramolecular reorganization within a short time frame during acclimation to an environmental change. This reorganization includes state transitions that balance the excitation of photosystem I and II by shuttling peripheral antenna proteins between the two, thermal energy dissipation that occurs at energy-quenching sites within the light-harvesting antenna generated for negative feedback when excess light is absorbed, and cyclic electron flow that is facilitated between photosystem I and the cytochrome bf complex when cells demand more ATP and/or need to activate energy dissipation. This review will highlight the recent findings regarding these environmental acclimation events in model organisms with particular attention to the unicellular green alga C. reinhardtii and with reference to the vascular plant A. thaliana, which offers a glimpse into the dynamic behavior of photosynthetic machineries in nature.